2022
DOI: 10.2337/dc21-1944
|View full text |Cite|
|
Sign up to set email alerts
|

Finerenone in Patients With Chronic Kidney Disease and Type 2 Diabetes According to Baseline HbA1c and Insulin Use: An Analysis From the FIDELIO-DKD Study

Abstract: OBJECTIVE Finerenone significantly improved cardiorenal outcomes in patients with chronic kidney disease (CKD) and type 2 diabetes (T2D) in the Finerenone in Reducing Kidney Failure and Disease Progression in Diabetic Kidney Disease trial. We explored whether baseline HbA1c level and insulin treatment influenced outcomes. RESEARCH DESIGN AND METHODS Patients with T2D, urine albumin-to-creatinine ratio (UACR) of 30–5,000 mg/g,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 31 publications
0
10
0
3
Order By: Relevance
“…9 This is an area with pressing unmet needs for a diverse population where minority groups bear a disproportionate burden. Yet, while an ideal estimate of representation in CKD clinical trials would suggest 35% as an enrollment target for Black or African American participants, 16 a survey of clinical studies reported in 2022 indicates most trials stand below that estimate, ranging between 5% and 29%, [17][18][19][20][21][22][23][24] and only one report showed 58.8% of African American participants. 25 This situation warrants a push for more inclusive research.…”
Section: Why Dei In Clinical Research?mentioning
confidence: 99%
“…9 This is an area with pressing unmet needs for a diverse population where minority groups bear a disproportionate burden. Yet, while an ideal estimate of representation in CKD clinical trials would suggest 35% as an enrollment target for Black or African American participants, 16 a survey of clinical studies reported in 2022 indicates most trials stand below that estimate, ranging between 5% and 29%, [17][18][19][20][21][22][23][24] and only one report showed 58.8% of African American participants. 25 This situation warrants a push for more inclusive research.…”
Section: Why Dei In Clinical Research?mentioning
confidence: 99%
“…After a mean follow-up of 2.6 years, relative to placebo, finerenone significantly reduced CKD progression (primary endpoint) by 18% (HR 0.82; 95% CI = 0.7–0.93; p = 0.001], and decreased the composite secondary endpoint (death from CV causes, non-fatal myocardial infarction, nonfatal stroke, or hospitalization for HF) by 14% (HR 0.86; 95% CI = 0.75–0.99) ( Table 3 ). The benefit of finerenone was independent of the history of CV disease [ 11 ], blood pressure [ 49 ] and HbA1c [ 50 ] levels, as well as the use of insulin [ 50 ], SGLT2 inhibitors [ 51 ] or glucagon-like peptide receptor type 1 (GLP1) agonists [ 52 ]. In a secondary analysis of the FIDELIO-DKD trial, finerenone reduced the risk of newly diagnosed atrial fibrillation/flutter compared with placebo (3.2% vs 4.5%; p = 0.016) [ 53 ].…”
Section: Finerenone Slows the Progression Of Ckd And Reduces The Risk...mentioning
confidence: 99%
“…Different trials also demonstrated a significant reduction in the primary outcome (CV death, non-fatal myocardial infarction, non-fatal stroke, or hospitalization for HF) in those subjects with T2DM and chronic kidney disease receiving finerenone [ 98 100 ]. Indeed, finerenone significantly improved cardiorenal outcomes in patients with T2DM and kidney disease irrespective of HbA1c levels or insulin use [ 101 ]. Therefore, finerenone should be considered for treatment of patients with T2DM, and this agent is likely to be included as an important treatment option in future updates of current guidelines.…”
Section: Hypertensionmentioning
confidence: 99%